Reminiscence therapy-based care program alleviates anxiety and depression, as well as improves the quality of life in recurrent gastric cancer patients - Wu, Xing; Zhang, Weiwei (Frontiers in Psychology, 2023)
Objective Reminiscence therapy is a non-drug method that eases psychological burden and enhances quality of life by memories and communications in cancer patients. This study aimed to evaluate influence of reminiscence therapy-based care program on anxiety, depression, and quality of life in recurrent gastric cancer patients. Methods Totally, 96 recurrent gastric cancer patients were randomly assigned as 1:1 ratio into reminiscence therapy-based care group (N = 48) and usual care group (N = 48) to receive 12-week corresponding interventions. Besides, all patients were follow-up for 6 months. Results Hospital Anxiety and Depression Scales-anxiety score at 4th month (p = 0.031) and 6th month (p = 0.004), Hospital Anxiety and Depression Scales-depression score at 6th month (p = 0.018), and anxiety severity at 4th month (p = 0.041) and 6th month (p = 0.037) were lower in reminiscence therapy-based care group than in usual care group. Quality of Life Questionnaire-Core 30 global health status score at 2nd month (p = 0.048), 4th month (p = 0.036), and 6th month (p = 0.014), Quality of Life Questionnaire-Core 30 function score at 4th month (p = 0.014) and 6th month (p = 0.021) were higher, while Quality of Life Questionnaire-Core 30 symptoms score at 2nd month (p = 0.041) and 4th month (p = 0.035) were lower in reminiscence therapy-based care group than in usual care group. Furthermore, reminiscence therapy-based care was more effective on improving mental health and quality of life in recurrent gastric cancer patients with anxiety or depression at baseline than those without. Conclusion Reminiscence therapy-based care serves as an effective intervention, which relieves anxiety and depression, and improves quality of life in recurrent gastric cancer patients.